Revitalizing abandoned coastal ponds in Indonesia: a waqf-based permaculture solution for sustainable aquaculture - Ahlis, Fatoni; Mega T.R., Luik; Adam Sa'ad, Auwal; Ferdi, Zanuar Azan (Department of Islamic Economic, IPB University, 2026)
This research proposes a sustainable model for revitalizing abandoned coastal ponds in Indonesia by integrating waqf and permaculture water design. Conventional industrial practices in coastal pond management, characterized by using artificial chemicals, have led to significant environmental degradation, contradicting Islamic principles. The study suggests utilizing cash waqf to fund permaculture pond — a method that collaborates with nature, avoiding artificial inputs and promoting ecological balance. By aligning with Islamic teachings on environmental stewardship, this model aims to restore land quality and productivity while benefiting coastal communities. Employing a qualitative methodology, the research utilizes secondary data from a range of sources to analyze the potential of this approach. The findings advocate for a waqf-based management system that ensures environmental sustainability and adheres to Islamic values, offering a viable alternative to harmful conventional practices.